CITY AND ‘COLONIAL GOVERNANCE’ IN LATE COLONIAL INDONESIA: TOWARDS AN AGENDA FOR HISTORICAL RESEARCH - Abdul Wahid (Paramita: Historical Studies Journal)
Urban history is a rich and challenging field of study, which is relatively new in Indonesia. In last decade, a body of literature have been produced which examine various aspects of Indonesian urban history of the colonial period. Yet, there are still many other aspects of Indonesian urban history that is still relatively unexplored and needs further research. One of them is that the concerns with the city management, institutional arrangement, and administrative system in general. These aspects are very important to be known not only to understand how cities were governed at the time, but also to see the continuity of their legacies in the subsequent period. Indonesian cities today inherit many kinds of institutional legacies, particularly from the colonial period. Through an extensive literature overview, this paper seeks to discuss several main aspects of city management system of urban Indonesia in late colonial period, based on which it proposes some important research agenda that needs to be carried out to complement our historical comprehension on Indonesian urban history.